2020
DOI: 10.1002/lio2.411
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve repair utilizing intraoperative repair strategies

Abstract: ObjectivesTo determine whether functional and anatomical outcomes following suture neurorrhaphy are improved by the addition of electrical stimulation with or without the addition of polyethylene glycol (PEG).MethodsIn a rat model of facial nerve injury, complete facial nerve transection and repair was performed via (a) suture neurorrhaphy alone, (b) neurorrhaphy with the addition of brief (30 minutes) intraoperative electrical stimulation, or (c) neurorrhaphy with the addition electrical stimulation and PEG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In recent years, an increasing number of studies have applied electrical stimulation to promote peripheral nerve repair. 53,[70][71][72][73] For example, Brown et al 74 have compared the repair effect of suturing the nerve alone with that of applying half an hour of electrical stimulation to the nerve at the time of suturing and their results showed that the addition of brief intraoperative electrical stimulation could effectively improve all functional outcomes. Willand et al 75 have also applied electrical stimulation to the gastrocnemius muscle by implanting electrodes for 1 month after transection of the tibial nerve, and the results showed that the introduction of electrical stimulation was effective at reducing muscle atrophy.…”
Section: Conventional Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have applied electrical stimulation to promote peripheral nerve repair. 53,[70][71][72][73] For example, Brown et al 74 have compared the repair effect of suturing the nerve alone with that of applying half an hour of electrical stimulation to the nerve at the time of suturing and their results showed that the addition of brief intraoperative electrical stimulation could effectively improve all functional outcomes. Willand et al 75 have also applied electrical stimulation to the gastrocnemius muscle by implanting electrodes for 1 month after transection of the tibial nerve, and the results showed that the introduction of electrical stimulation was effective at reducing muscle atrophy.…”
Section: Conventional Electrical Stimulationmentioning
confidence: 99%
“…87 Conductive materials can modulate cell-cell or cell-tissue interactions by mediating electrical charge transport at the interface of cell membranes, 87 and electrogenic materials can provide electrical stimulation to nerve cells or other types of cells to stimulate them to generate action potentials. 74,88 At present, many studies have confirmed that electroactive materials play an important role in peripheral nerve repair, such as the regulation of cell behaviors, signaling pathway, immune microenvironment, etc. A detailed overview is listed in Table 2.…”
Section: Role Of Electroactive Materials In Peripheral Nerve Repairmentioning
confidence: 99%